2000
DOI: 10.1007/s002510000216
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of α 2 -macroglobulin from a bony fish, the common carp ( Cyprinus carpio ): striking sequence diversity in functional sites

Abstract: Unlike mammals, bony fish possess multiple genes encoding the complement component C3, a member of the alpha2-macroglobulin (alpha2M) protein family, presumably expanding the diversity of immune recognition. To examine whether the alpha2M gene has also duplicated and diverged in the bony fish lineage, cDNA cloning of alpha2M from a pseudotetraploid teleost, the common carp (Cyprinus carpio), was conducted and resulted in the isolation of three distinct alpha2M sequences from a single individual, indicating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…There is a possibility that grass carp a 2 M is encoded by multiple genes. According to previous reports, Limulus has two different forms, which are present in a ratio of 2:1 [14], and three different forms have been reported in common carp [7].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is a possibility that grass carp a 2 M is encoded by multiple genes. According to previous reports, Limulus has two different forms, which are present in a ratio of 2:1 [14], and three different forms have been reported in common carp [7].…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we found that grass carp a 2 M may be composed of two different subunits, with molecular weights of 95 kDa and 80 kDa. Reports on a 2 M for the common carp [7], indicate that it consists of two subunits with M r of 93 kDa and 85 kDa. a 2 M differs from other large protease inhibitors in the mechanism by which it inhibits protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the number of chromosomes (e.g., the common carp, 2n ϭ 100 (50 pairs of chromosomes); the tench Tinca tinca, 2n ϭ 48; the barbel steed Hemibarbus labeo, 2n ϭ 50; the grass carp Ctenopharyngodon idellus, 2n ϭ 48 (data from FishBase, ͗www.fishbase.org/͘)), the common carp is believed to have arisen by allotetraploidization 12-50 million years ago in the cyprinid family (42)(43)(44). Hence, it seems reasonable to assume that the tetraploidization has probably contributed, at least in part, to the gene duplications of other members of the thioestercontaining protein family, such as C3, C5, and ␣ 2 M, of this species (21)(22)(23). However, it is unlikely that carp C4-1 and C4-2 were generated by the tetraploidization event as judged from their substantial sequence divergence.…”
Section: Discussionmentioning
confidence: 99%
“…probe, representing 2925-3136 of carp ␣ 2 M-1 (23). Of the 20 clones that were negative to both probes, one clone (Cp1) showed closer similarity to human and Xenopus C4 than to C3 and ␣ 2 M (Fig.…”
Section: Isolation Of Cdna Clones Encoding Carp C4mentioning
confidence: 99%
See 1 more Smart Citation